(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article provides a comprehensive and analytical study of the independence of the Republic of Uzbekistan and the establishment of its national symbols as key expressions of statehood and identity. It traces the historical process from the declaration of independence on August 31, 1991, to the adoption of the flag, emblem, and anthem, which symbolize unity, sovereignty, and cultural continuity. Supported by constitutional laws, historical archives, and scholarly works, the paper highlights how these symbols are deeply intertwined with Uzbekistan’s ancient heritage, modern reforms, and aspirations for global integration.